Gender panic, gender policy - Demos, Vasilikie P.; Segal, Marcia Texler, 1940- (Advances in gender research ;, 2017)
Using diverse theories and methods including analysis of on-line data, feminist critical discourse, fieldwork, grounded theory, and queer theory, this volume explores gender panic and policy in the United States and beyond.